The Visual Intelligence of PSGCC Gifted Child Community at Yogyakarta - Ardiyawan, Ardiyawan; Syarif, Muh Ibnan; Triyanto, Triyanto (Universitas Negeri Semarang, 2018)
In art education, through psychological perspective, the intellectuality of a gifted child is a possible influence to the projected expression in their drawing. ChildrenÃ¢â‚¬â„¢s intelligence allows them to freely visualize their creativity on the canvas. In this context, this research aims to analyse Ã¢â‚¬Å“The Visual Intelligence of PSGCC Gifted Child Community at YogyakartaÃ¢â‚¬Â. The research employed qualitative methods and utilized case study design. The data of the research were from observation, interview, and documentation. Further, the researcher conducted triangulation of sources and data to validate the findings. The analysis of the data was through the sequence of data reduction, presentation, and verification. The findings of the research showed that the gifted children in the PSGCC community had the tendency of possessing visual intelligence with some details to discuss. First, the existence of the visual intelligence of the gifted children from PSGCC community shows that the children have the sensitivity to visual elements (lines, colours, shapes, and spaces); that is to say, the children are able to compose the element and visual principle in accordance with their behalf. Second, the visual intelligence of the children is visible from the way they identify an object to paint, starting from describing the position of the object, identify the part of the object, and recognize the characteristic of the object. Third, the visual intelligence from the children portrays that the childrenÃ¢â‚¬â„¢s ability to comprehend and portray a dimension of an object as well as its surrounding. The researchers expect that this research gives an implication to become a reference for parents, teachers, and children communityÃ¢â‚¬â„¢s liaisons to observe and acknowledge the intelligence of children through their paintings.